2016
DOI: 10.3329/bjo.v21i2.27648
|View full text |Cite
|
Sign up to set email alerts
|

Status of Ossicles in Cholesteatoma

Abstract: The study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…8 Present research found that ossicular chain was intact in 33% cases whereas 67% cases had eroded ossicular chain. Similar results were obtained by Hossain et al study and Rao et al 9,12 While contrary observations were reported by Bangera et al where 65% cases were intact and only 29% cases were eroded. 8 Our study evaluated that malleus was found intact in 78 (78%), 18 (18%) had erosion of the malleus handle and erosion involved the head of malleus in 4% cases.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…8 Present research found that ossicular chain was intact in 33% cases whereas 67% cases had eroded ossicular chain. Similar results were obtained by Hossain et al study and Rao et al 9,12 While contrary observations were reported by Bangera et al where 65% cases were intact and only 29% cases were eroded. 8 Our study evaluated that malleus was found intact in 78 (78%), 18 (18%) had erosion of the malleus handle and erosion involved the head of malleus in 4% cases.…”
Section: Resultssupporting
confidence: 86%
“…Similarly, Hossain et al noted intact stapes in 55% cases and eroded in 45% cases. 9 Varshney et al also reported intact stapes in 78.67% cases and involvement of stapes supra-structure was noted in 21.33% cases of CSOM. 1 Bangera et al also reported intact stapes in 77% cases and supra-structure was eroded in 23% cases.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…90% cases showed ossicular erosion while only 10% cases showed intact ossicles. 3 In present study maximum number of patients presented with complaints of discharging ear (84%) followed by hearing impairment (64%) and then followed by ear ache (48%), headache (32%) swelling around the ear (20%), fever (24%) and tinnitus in (12%) cases. Sade et al also found in their series that otorrhoea was the most common symptom in 62% cases followed by hypoacuris (11%) cases.…”
Section: Discussionmentioning
confidence: 52%
“…4 Partial or total destruction of ossicles is seen in approximately 80% of patients with cholesteatoma, whereas in chronic otitis media without cholesteatom, ossicular chain erosion can be seen in approximately 20% cases. 3 Imaging plays an important role, especially in complicated and recurrent conditions imaging findings may fundamentally influence the treatment. Also, in noninflammatory conditions of external and middle ear computed tomography (CT) or magnetic resonance imaging (MRI) would provide a diagnosis and/or necessary information for surgery in a significant number of cases.…”
mentioning
confidence: 99%